CHARACTER OF THE HUMAN IN ENGLISH AND UZBEK LANGUAGES (Conferencea, 2024)
The article defines linguistic peculiarities of phraseological units denoting to human character in English and Uzbek languages. There are several examples from literary sources in order to analyze them clearly. Phraseological units play a special role in seeing the world through the use of language tools.